IMPLEMENTASI WEB SITE PENGOLAHAN DATA ALUMNI DAN INFORMASI LOWONGAN KERJA DI SMK 3 PANGKALPINANG - Marini Marini; Sarwindah Sarwindah; Tri Sugihartono; Fitriyani Fitriyani (J-Icon : Jurnal Komputer dan Informatika, 2021)
Alumni Data Collection at Vocational High School 3 (SMK 3) Pangkalpinang previously existed but was still done in writing using the Microsoft Word application so that it experienced several problems such as errors in data collection, archiving difficulties, delays in obtaining alumni information and lack of job vacancies information. Making this website serves to track the whereabouts of alumni through the internet network and obtain alumni data collection information, the whereabouts of alumni workplaces quickly. The information displayed on this website is the profile of the school, alumni, job vacancies and activities that will be held at the school, especially those related to alumni. This information can be accessed by alumni and other external parties. The method used to design this website is a software development model using a Framework or Application of Systems Technology (FAST) model which consists of scope definition, problem analysis, requirements analysis and prior design. The database used is MySql and the tool used to develop it is the Unified Modeling language. The result of this research is a website that functions as a means of interaction between schools and alumni, promoting schools and processing alumni data